Problems of Coordination in Agricultural Programmes - Planning Commission (Planning Commission, 1965)
Coordination is not a new or unfamiliar area of study as far as the Programme Evaluation Organisation is concerned. In a number of its evaluation reports, the P.E.O. has invited attention to the problem areas of coordination in the implementation of community development and other rural programmes. The focus of the past studies has, by and large, been on coordination among different agencies involved in the execution of various schemes and projects. In the present study, undertaken mainly at the instance of the Ministry of Food. & Agriculture, a slightly different approach has been adopted, in the sense that coordination has been looked at in the perspective of the totality of jobs, decisions, activities and events that provide the full picture of implementation' of agricultural programmes. In this functional approach, coordinated implementation of an agricultural programme, properly conceived and planned, involves the working out of a detailed programme of action, and the systematic pursuit of this, jointly as well as severally by the different agencies concerned with it. As the field work for this study proceeded, it became clear that such a study required a much more thorough and prolonged enquiry than could be given to it. In a sense, this report has some elements of a pilot nature.
Programme Evaluation Organisation Planning Commission Govt. of India